Legal problem and resolution survey, 2014-2015 (UK Data Service, 2017)
The Legal Problem and Resolution Survey, 2014-2015 (LPRS), builds on the English and Welsh Civil and Social Justice Survey (CSJS) and Civil and Social Justice Panel Survey (CSJPS), a series of surveys conducted between 2001 and 2012. As a number of significant reforms have been made to the civil, family and administrative justice systems recently, there was a need to adapt and develop previous versions of the questionnaire to ensure it more closely met current policy objectives. LPRS collected information about the prevalence of civil, administrative and family legal problems, the characteristics of these problems and the people experiencing them, and the problem outcomes. The survey also covered the help and advice people obtained to resolve problems and the resolution strategies that they used. Further information about this survey can be found on gov.uk Publications webpage.